BIBHATSA RASA AND THE AESTHETICS OF PURIFICATION: AN INQUIRY INTO THE SPIRITUAL AND MORAL DIMENSIONS OF DISGUST IN SANSKRIT DRAMATURGY - Naik, Babuli (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study examines the philosophical and aesthetic significance of Bibhatsa Rasa—the sentiment of disgust—within the framework of Sanskrit dramaturgy, focusing on its exposition in Bharata’s Nāṭyaśāstra and its elaboration by Abhinavagupta in the Abhinavabhāratī. Traditionally perceived as a negative emotion, disgust is recontextualized in Indian aesthetic theory as a vital component of the rasa experience, contributing to the spectator’s moral and spiritual edification. The analysis begins by exploring the structural components of Bibhatsa Rasa, including its sthāyibhāva (permanent emotion) of jugupsā (revulsion), along with its associated vibhāvas (determinants), anubhāvas (consequents), and vyabhicāribhāvas (transitory states). It then delves into the process of sādhāraṇīkaraṇa (universalization), through which personal emotions are transformed into aesthetic experiences, allowing the audience to engage with repulsive themes in a contemplative manner. Drawing upon Abhinavagupta’s insights, the paper argues that the aesthetic experience of disgust catalyses self-reflection and ethical awareness. By confronting the abject and the morally reprehensible within a controlled artistic context, spectators are prompted to reaffirm societal values and personal virtues. This engagement facilitates a form of emotional purification (śuddhi), aligning with the broader objectives of Indian dramaturgy to entertain and elevate the audience’s consciousness. Through textual analysis and philosophical inquiry, this research highlights the integral role of Bibhatsa Rasa in the moral and spiritual dimensions of Sanskrit theatre. It underscores the nuanced understanding of emotions in Indian aesthetics, where even sentiments like disgust are harnessed to foster ethical introspection and spiritual growth.